Indicators of food and water security in an Arctic Health context - results from an international workshop discussion - Nilsson, Lena Maria; Berner, James; Dudarev, Alexey A.; Mulvad, Gert; Odland, Jon Øyvind; Parkinson, Alan; Rautio, Arja; Tikhonov, Constantine; Evengård, Birgitta (International Journal of Circumpolar Health, 2013)
In August 2012, a literature search with the aim of describing indicators on food and water security in an Arctic health context was initialized in collaboration between the Arctic Human Health Expert Group, SDWG/AHHEG and the AMAP (Arctic Monitoring and Assessment Programme within the Arctic Council) Human Health Assessment Group, AMAP/HHAG. In December 2012, workshop discussions were performed with representatives from both of these organizations, including 7 Arctic countries. The aim of this article is to describe the workshop discussions and the rational for the 12 indicators selected and the 9 rejected and to discuss the potential feasibility of these. Advantages and disadvantages of candidate indicators were listed. Informative value and costs for collecting were estimated separately on a 3-level scale: low, medium and high. Based on these reviews, the final selection of promoted and rejected indicators was performed and summarized in tables. Among 10 suggested indicators of food security, 6 were promoted: healthy weight, traditional food proportion in diet, monetary food costs, non-monetary food accessibility, food-borne diseases and food-related contaminants. Four were rejected: per-person dietary energy supply, food security modules, self-estimated food safety and healthy eating. Among 10 suggested indicators of water security, 6 were promoted: per-capita renewable water, accessibility of running water, waterborne diseases, drinking-water-related contaminants, authorized water quality assurance and water safety plans. Four were rejected: water consumption, types of water sources, periodic water shortages and household water costs.